Uji Aktivitas Tangkai Daun Pepaya Sebagai Antibakteri Escherichia coli - Alif Rahman Habibi; Willy Anthony Iqnatius Wullur; Victor E D Palapessy; Rifadhil Akbar Maulana (JURNAL ILMIAH KESEHATAN MASYARAKAT DAN SOSIAL, 2024)
Papaya Carica papaya L. is a fruit commodity that has many functions and benefits as cooking, sweets, medicine, snacks. Secondary metabolite compounds found in Carica papaya L. papaya are flavonoids, polyphenols, quinones and tannins. It is known that falvonoid compounds can have antibacterial properties. In this research, it is hoped that papaya leaf stalk extract can act as an antimicrobial so that it can be used as first aid for diseases caused by E. coli bacteria. This research used ingredients from 500 grams of papaya leaf stalk extract which had been macerated using 96% ethanol, to produce a thick extract. The thick extract was tested on NA growth media using E. coli bacteria. In this study, the clear zone produced at a concentration of 50% was 7 mm, at a concentration of 25% it produced a clear zone of 6 mm and at a concentration of 12.5% it did not produce a clear zone.